Endoscopic correction of obstructive complications after HIFU-ablation of the prostate with holmium laser - Popkov V.M.; Fomkin R.N.; Shatylko T.V. (Саратовский научно-медицинский журнал, 2018)
Purpose: to improve the results of treatment of the obstructive complications (an urethra stenosis, a bladder neck sclerosis) caused by application of the high-intensity focused ultrasonic ablation (HIFU) concerning treatment of the localized prostate cancer. Material and Methods. An object of the research included 41 patients, with the infravesical obstruction (IVO) which has arisen in the postoperative period to which elimination the holmium laser is used. Results. The bladder neck was the most frequent place of obstruction. Average time before emergence of the first episode of IVO: 8.2±1.3 months. Distinctions on time before development of an episode of IVO depending on the fact of carrying out TURP before HIFU not confirmed (p=0.440). More advanced age for a moment HIFU-ablation has been associated with much higher frequency of IVO (p=0.021). Considerably smaller frequency repeated was observed by IVO at a larger ratio transurethral resection to the initial volume of a prostate (p=0.031). Duration of a laser endoscopic ure-throtomy was 27 [10-70] minutes, serious perioperative or postoperative complications were not determined. Average term before removal of a catheter of Foley: 3 [1-5] days, hospitalization duration included 4 [3-6] days. After treatment considerable improvement on indicators of the maximum speed of a stream of urine (Qmax) and volume of residual urine was observed. The total score according to the questionnaires of IPSS and QoL has considerably improved, significant changes on symptoms of accumulation are noted. After the first holmium laser urethrotomy of 80.4% of patients have noted satisfactory results without recurrence of IVO; 19.6% of patients were required a repeated laser endoscopic urethrotomy. Recurrence term after the first laser urethrotomy is on average equal to 2.5 months. Conclusion. The endoscopic urethrotomy by means of the holmium laser is safe, effective and minimum invasive type of treatment of a stenosis of a neck of the bladder / urethra after ablative cancer therapy of prostate. The advantages are the minimum of traumas of surrounding tissues and preservation of the mechanism of deduction of urine.